Odpowiedzi

2010-02-01T16:33:44+01:00
1.
6x - 2y = 9
3x + y - 4,5=0 |*2

6x-2y=9
6x+2y=9
___
12x=18 |:12
x= 12/18=2/3
2010-02-01T16:35:52+01:00
6x - 2y = 9
3x + y = 4,5 \ * (-2)

6x - 2y =9
-6x -2y = - 9

-4y=0
y=0

6x -0 =9
x= 6/9
x= 2/3


0,1x - 0,2y = 0,7 \ * 20
- 2 x + 4y = -14

2x - 4y = 14
-2x + 4y = - 14

0=0

Najlepsza Odpowiedź!
2010-02-01T16:40:30+01:00
A)
6x-2y=9
3x+y-4,5=0

6x-2y=9
3x+y=4,5|*2

6x-2y=9
6x+2y=9
12x=18
x=1,5

6*1,5-2y=9
9-2y=9
-2y=0
y=0

b)
0,1x-0,2y=0,7|*20
-2x+4y=-14

2x-4y=14
-2x+4y=-14

0=0